Blended Learning Models to Improve Student Learning Outcomes During the Covid-19 Pandemic - Agustina, Ayuda Nia (KnE Life Sciences, 2021)
The COVID-19 pandemic has affected various aspects of life, one of which is education. Direct face-to-face contact needs to be reduced to prevent transmission of COVID-19, while educational institutions must continue to organize learning courses. This study identifies the effect of the blended learning model on learning outcomes of level II students in child-nursing courses during the COVID-19 pandemic. This study used a pre-experiment, one-group pre-test post-test, the sample was selected using the cluster random sampling method involving 105 students of level II of the Fatmawati Academy of Nursing. Data were analyzed using SPSS-24 software with the Wilcoxon test. The instrument used was a written test consisting of a pre-test and a post-test, a child-nursing procedure skills test. The results showed pre-test mean value is 74.74 and post-test mean value is 80,133. From these results, it can be concluded that there is the use of the blended learning model improved the learning outcomes of child nursing in Fatmawati Nursing Academy students during the COVID-19 pandemic. This can be seen from the average post-test result value, which is higher than the pre-test result value (p = 0.000). Keywords: Blended learning, COVID-19, student learning outcomes, pandemic, learning